Matching-adjusted indirect comparison of axi-cel and liso-cel in relapsed or refractory large B-cell lymphoma. Issue 13 (10th November 2022) - Oluwole, Olalekan O.; Chen, Jenny M.H; Chan, Keith; Patel, Anik R.; Jansen, Jeroen P.; Keeping, Sam; Zheng, Yan; Snider, Julia T.; Locke, Frederick L.
Abstract: In the absence of a randomized head-to-head trial, an unanchored matching-adjusted indirect comparison was performed to estimate the relative treatment effects of axicabtagene ciloleucel (axi-cel; ZUMA-1) versus lisocabtagene maraleucel (liso-cel; TRANSCEND-NHL-001) for treatment of relapsed/refractory (R/R) large B-cell lymphoma (LBCL) after at least two lines of therapy. After matching, axi-cel and liso-cel had comparable objective response rates and duration. Compared to liso-cel, axi-cel was associated with improvements in overall survival (hazard ratio [HR]: 0.53 [95% CI: 0.34–0.82]) and progression-free survival (HR: 0.61 [95% CI: 0.40–0.92]). Axi-cel was associated with a higher rate of grade ≥3 cytokine release syndrome (odds ratio [OR]: 3.64 [95% CI: 1.04–12.76]) and neurological events (OR: 3.45 [95% CI: 1.65–7.19]), with smaller differences estimated in scenario analyses including ZUMA-1 safety management cohorts. Results suggest axi-cel improved survival compared to liso-cel but with increased odds of specific adverse events.